Primula subpyrenaica (Primulaceae) a new species from the Pyrenean range (south-western Europe) - Aymerich, Pere; López-Alvarado, Javier; Sáez, Llorenç (Phytotaxa, 2014)
A new species in the genus Primula, P. subpyrenaica, is described from the Pyrenean range in the north-eastern Iberian Peninsula. The species belongs to P. sect. Auricula, and is related to P. auricula and P. lutea mainly on a morphological basis. However, P. subpyrenaica differs from those two species and from other related taxa by various morphological characters (non-scariose and longer bracts, fragrant leaves, yellowish or brownish when pressed). Data on its ecology, taxonomic relationships and conservation status of this narrow endemic is also provided.